Ambiente sonoro : organização dos sons e pertença no contexto escolar de um grupo de adolescentes do Colégio San Petrus - Primavera do Leste/MT - Ipolito, Luiz Francisco de Paula (2022)
This scientific investigation, linked to the postgraduate program in Contemporary Culture Studies - ECCO/UFMT, proposed an evaluation and discussion in relation to the sound environment in a private school context in the city of Primavera do Leste/MT, Colégio San Petrus. The group of subjects of this research comprised 21 adolescents aged 13 years on the first half of 2021. It is proposed as specific objectives: carrying out a bibliographic study involving sound events, their organization and belonging; investigating the organization of school sound events; verifying from the relationship that this group of adolescents establishes with the environment and the sound. The methodology used includes participant qualitative research, in which participants play active role with the researcher. The bibliographic research was based on research and studies about sound and the environment by the following authors: Schafer (2001); (2011); (2020); Borges (2008); (2014); Vertamatti (2008); Eder (2003); Hall (2003); Mattoso (1998); Moraes (2015). The discussion involved the concept of soundscape, sound environment and its specificities in the musical field with regard to human beings and their interaction with the environment, and information was collected through activities and a questionnaire regarding how a group of adolescents perceived, transcribed and organized the sounds of the school environment, as well as their feeling of belonging to the place. The historical contextualization both in reference to the visual arts and music were important to understand the avant-garde movements and the ruptures with the traditional. With regard to familiarization with contemporary music and belonging to the school environment, several paths were pointed out mainly due to the pandemic scenario. Another very relevant point was the formation of small groups throughout the research process.